KETIKA INDEPENDENSI MENJADI TOLAK UKUR KUALITAS AUDIT - Fauziyah, Tias Rahmi (RISTANSI: Riset Akuntansi, 2024)
This study emphasizes that an auditor's independence can support the outcomes of the audit report, thereby serving as a benchmark for audit quality. The type of research used is qualitative research with a literature review approach by seeking information through books, journals, and other literature. The research findings reveal several approaches to measuring audit quality, including process quality, result quality, and follow-up quality. Result and process oriented approaches are better able to illustrate how auditors perform their work to achieve a measurable audit quality. Auditor independence is divided into three aspects: independence in fact, independence in appearance, and independence in expertise or competence. The higher independence of an auditor, the more it can enhance the quality of the audit performed. Audit standards emphasize not only the importance of independence in conducting audits but also the aspects of appearance and the reality of that independence.